Pembiayaan Iklim di Asia Timur dan Pasifik dari Perspektif Tata Kelola dan Kesulitan Keuangan - Afifah, Nurul; Nugraha, Nugraha; Heryana, Toni; Supriatna, Yayat; Nkansah, Obed Kwabina Opoku (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
This study analyses the influence of governance and financial distress on climate funding in East Asia and the Pacific (EAP). A multiple linear regression analysis was undertaken using panel data from 12 EAP nations between 2015 and 2021 to investigate the links between governance, financial distress, and climate finance. The results demonstrate that governance structures are more successful in obtaining climate related funds. Additionally, financial challenges show a notable positive correlation, indicating that financially struggling nations tend to attract more global climate funds, possibly due to their limited domestic capacities for addressing climate change. The regression analysis explained 85.71% of the variations in climate finance, underscoring the importance of governance and financial conditions in influencing how climate finance is distributed within the region. These findings underscore the need of robust governance and financial stability in maximizing the use of climate finance for mitigation and adaptation initiatives.